RITUAL BAAYUN ANAK DAN DINAMIKANYA - Emawati Emawati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2016)
This article attempts to shed light on the concept and ritual connected with Baayun Anak or in Dayak society. The research is based on fieldwork conducted from 2012 to 2013 in Dayak village in Sampit, Central Kalimantan. Baayun Anak which develops today has the sustainability challenge in order to remain to exist. There are some findings of the research as follows: first, the Baayun Anak has been a cultural tradition of Dayak tribe in Kalimantan since the days of their ancestors whose religion was Kaharingan. After Islam came in the sixteenth century AD, the Islamic culture and the Baayun Anak tradition turned out to complete each other and develop in harmony. Second, baayun anak change in the middle of continuity. The change concerns the people's views on the practice of life in this case Baayun anak associated with changes in experience. In this case there are a few things associated with these changes, among others, the fact that the ritual Baayun Anak has undergone various changes, more emphasis towards the present situation.Keywords: Tradition, Dinamic Culture, Baayun Child